Analysis of the effects of coordination program viva 2 parkinson (CoVi2) on dynamic balance, muscle parameters, and symptomatology in older adults diagnosed with advanced stages of parkinson⇔s disease a case study - Pereira-Pedro, Karina Pitombeira [UNESP]; Mollinedo-Cardalda, Irimia; Carral, José Maria Cancela (Wolters Kluwer, 2021)
There is evidence to suggest that assisted cycling can effectively improve the motor function of patients with Parkinson’s disease (PD) and an assisted cycling intervention is more beneficial for those with more advanced PD. Therefore, the aim of this study was to investigate the influence of an intervention with a coordination program at MOTOmed Viva 2 Parkinson on dynamic balance, muscle parameters, and symptoms in elderly people diagnosed with advanced stages of PD. We studied 4 elderly people with PD in advanced stages. We evaluated PD symptomatology using the adapted Spanish version of the MDS-UPDRS (Movement Disorder Society Unified Parkinson’s Disease Rating Scale); dynamic balance was evaluated by means of the Timed Up and Go (TUG) and the MOTOmed Viva 2 Parkinson system stores data about muscle tone, symmetry, coordination, and spasms, in each of the sessions undertaken. We found that a 21-minute coordination training in 13 sessions with the MOTOmed device demonstrates positive effects on muscle tone, spasms, coordination, symmetry, and balance in older adults diagnosed with advanced stages of PD.
Keywords: Cycling; Neurodegenerative diseases; Older adults; Physical activity